Nutritional effects of different calcium sources on growth of oil palm seedlings under nursery condition - Jamaludin, Nurul Mayzaitul Azwa; Musa, Mohamed Hanafi; Abu Seman, Idris; Khayat, Mohd Ezuan; Muhamad Tajudin, Nur Shuhada (Universiti Putra Malaysia Press, 2022)
Calcium (Ca) is an essential secondary macronutrient which necessary plant mineral frequently added to fertilizers to promote plant development and resistance to abiotic and biotic stressors. Applying Ca to soils suffices to meet crops’ Ca requirements. Regrettably, its function is obscure. Thus, it is critical to maintain enough nutrient availability through fertilizers or alter the soil environment for oil palm seedlings to grow and thrive. This study investigates the effects of different Ca sources on vegetative growth in oil palm seedlings. This experiment was carried out for nursery evaluation using 5-months old of oil palm seedlings with varying sources of Ca (C1–calcium chloride, CaCl2; C2–calcium sulfate, CaSO4; C3-calcium nitrate, CaNO3; C4–calcium carbonate, CaCO3; C5–calcium oxide, CaO, C6–calcium hydroxide, Ca(OH)2; and C7–water leach purification and neutralization underflow, NUF-WLP) and grown in a polybag containing beach ridges interspersed with swales (BRIS) soil within six months in Malaysian Palm Oil Board (MPOB) nursery, Seksyen 15, Bandar Baru Bangi. Five concentration levels of Ca (T1–200 ppm, T2–250 ppm, T3–300 ppm, T4–1,000 ppm, and T5–1,500 ppm) were used in a completely randomized design (CRD) with ten replications for each. Based on the total biomass of oil palm seedlings at 24 weeks after treatment with various sources of Ca, the result confirmed that C2 oil palm seedlings were more significant in size and denser at the root than other Ca types. The result is an essential indicator that C2 effectively increased the total biomass of oil palm seedlings at 1,000 ppm of Ca (T4); hence it was the best Ca source to improve the growth and development of oil palm seedlings throughout the experimental period at p≤0.05.